Whole brain radiation therapy alone versus radiosurgery for patients with 1-10 brain metastases from small cell lung cancer (ENCEPHALON Trial): study protocol for a randomized controlled trial - Bernhardt, Denise; Hommertgen, Adriane; Schmitt, Daniela; El-Shafie, Rami; Paul, Angela; König, Laila; Mair-Walther, Johanna; Krisam, Johannes; Klose, Christina; Welzel, Thomas; Hörner-Rieber, Juliane; Kappes, Jutta; et al. (Trials, 2018)
Conventional whole brain radiotherapy (WBRT) has been established as the treatment standard in patients with cerebral metastases from small-cell lung cancer (SCLC), however, it has only modest efficacy and limited prospective data is available for WBRT as well as local treatments such as stereotactic radiosurgery (SRS).
Published online: 16 July 2018
Gesehen am 26.07.2018